Influenza A Virus in Swine: Epidemiology, Challenges and Vaccination Strategies - Mancera Gracia, José Carlos; Pearce, Douglas S.; Masic, Aleksandar; Balasch, Monica (Frontiers in Veterinary Science, 2020)
Influenza A viruses cause acute respiratory infections in swine that result in significant economic losses for global pig production. Currently, three different subtypes of influenza A viruses of swine (IAV-S) co-circulate worldwide: H1N1, H3N2 and H1N2. However, the origin, genetic background and antigenic properties of those IAV-S vary considerably from region to region. Pigs could also have a role in the adaptation of avian influenza A viruses to humans and other mammalian hosts, either as intermediate hosts in which avian influenza viruses may adapt to humans, or as a “mixing vessel” in which influenza viruses from various origins may reassort, generating novel progeny viruses capable of replicating and spreading among humans. These potential roles highlight the importance of controlling influenza A viruses in pigs. Vaccination is currently the main tool to control IAV-S. Vaccines containing whole inactivated virus (WIV) with adjuvant have been traditionally used to generate highly specific antibodies against hemagglutinin (HA), the main antigenic protein. WIV vaccines are safe and protect against antigenically identical or very similar strains in the absence of maternally derived antibodies (MDAs). Yet, their efficacy is reduced against heterologous strains, or in presence of MDAs. Moreover, vaccine-associated enhanced respiratory disease (VAERD) has been described in pigs vaccinated with WIV vaccines and challenged with heterologous strains in the US. This, together with the increasingly complex epidemiology of SIVs, illustrates the need to explore new vaccination technologies and strategies. Currently, there are two different non-inactivated vaccines commercialized for swine in the US: an RNA vector vaccine expressing the HA of a H3N2 cluster IV, and a bivalent modified live vaccine (MLV) containing H1N2 γ-clade and H3N2 cluster IV. In addition, recombinant-protein vaccines, DNA vector vaccines and alternative attenuation technologies are being explored, but none of these new technologies has yet reached the market. The aim of this article is to provide a thorough review of the current epidemiological scenario of IAV-S, the challenges faced in the control of IAV-S infection and the tools being explored to overcome those challenges.